2021
DOI: 10.1101/2021.02.16.431370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intra-ocular dendritic cells are increased in HLA-B27 associated acute anterior uveitis

Abstract: Uveitis describes a heterogeneous group of inflammatory eye diseases characterized by infiltration of leukocytes into the uveal tissues. HLA-B27-associated Uveitis is a common subtype of uveitis and a prototypical ocular autoimmune disease. Local immune mechanisms driving human uveitis are poorly characterized mainly due to the limited available biomaterial and subsequent technical limitations. Here, we provide the first high-resolution characterization of intraocular leukocytes in HLA-B27 positive and negativ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
1
1
0
Order By: Relevance
“…Indeed, emerging single cell analysis of ocular fluids of patients support the infiltration of CD1c+ DC subsets in the eye during autoimmune uveitis (42), and we show that these cells express CD36 and CX3CR1 (Fig. 4G).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Indeed, emerging single cell analysis of ocular fluids of patients support the infiltration of CD1c+ DC subsets in the eye during autoimmune uveitis (42), and we show that these cells express CD36 and CX3CR1 (Fig. 4G).…”
Section: Discussionsupporting
confidence: 56%
“…We speculated that the decrease in blood CD36+CX3CR1+ CD1c+ DCs was a result from migration of these cells to the eye during autoimmune uveitis. Recent single-cell RNA sequencing data by Kasper and co-workers in eye biopsies of autoimmune uveitis patients show infiltration in the eye by conventional dendritic cells, which are transcriptionally similar to CD1c+ DCs (42). Reanalysis of this data using CLEC10A as a specific marker for CD1c+ DCs in tissues (43) showed that eye-infiltrating CD1c+ DC cells express CD36 and CX3CR1 (Fig.…”
Section: A Cd36+cx3cr1+cd1c+ Dc3 Subset Is Decreased In Autoimmune Uveitismentioning
confidence: 89%